1989
DOI: 10.1677/joe.0.1210351
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile growth hormone, insulin-like growth factors and antler development in red deer (Cervus elaphus scoticus) stags

Abstract: Plasma samples taken every 30 min over a 26-h period each month from six 4- to 15-month-old red deer stags were analysed for GH. In addition, two samples taken at 10.00 and 22.00 h were analysed for insulin-like growth factor-I (IGF-I) and insulin-like growth factor-II (IGF-II). A concentrate diet was available ad libitum. Food intake, body weight and antler status were recorded. Concentrations of GH were analysed using the PULSAR peak detection routine. Secretion of GH was pulsatile in every month of sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…Furthermore, concentrations of IGF-I are higher during growth (Suttie et al 1989) and are reduced during periods of restricted nutrition and fasting (McGuire et al 1992, Thissen et al 1994 and during infection and disease (Elsasser et al 1988(Elsasser et al , 1995. Therefore, it was reasoned that calves recovering at a faster rate would have higher concentrations of IGF-I in their plasma.…”
Section: Figurementioning
confidence: 99%
“…Furthermore, concentrations of IGF-I are higher during growth (Suttie et al 1989) and are reduced during periods of restricted nutrition and fasting (McGuire et al 1992, Thissen et al 1994 and during infection and disease (Elsasser et al 1988(Elsasser et al , 1995. Therefore, it was reasoned that calves recovering at a faster rate would have higher concentrations of IGF-I in their plasma.…”
Section: Figurementioning
confidence: 99%
“…These include changes in secretion of hormones involved in the reproductive (Lincoln & Kay 1979, Suttie et al 1992) and growth and metabolic (Suttie et al 1989) axes. Changes in behaviour at this time include increased aggression (Suttie 1985) and a reduced voluntary food intake (Loudon et al 1989) resulting in pronounced weight loss (Kay 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Partial amino acid sequence determination and a receptor-binding assay for red deer GH have suggested that the structure and function of deer GH are similar to those of other ruminant GHs (Curlewis et al 1992). The red deer is interesting in that the pattern of GH secretion appears to be correlated with the seasonal growth pattern of the animal (Suttie et al 1989, Curlewis et al 1992, Webster et al 1996. Here we describe the cloning and sequencing of the red deer GH gene, and relate this to the pattern of GH evolution seen in the Artiodactyla.…”
Section: Introductionmentioning
confidence: 83%
“…The sequence similarity among ruminant GHs also suggests that red deer GH is unable to bind to lactogenic sites, since ovine GH shows negligible binding to the red deer PRL receptor (Jabbour et al 1996). GH secretion in red deer is pulsatile and shows marked seasonal changes, with an increased mean plasma level in spring correlated with elevated insulin-like growth factor-I (IGF-I) levels and increases in liveweight gain and antler growth (Suttie et al 1989, Curlewis et al 1992,  3. Phylogenetic tree for mammalian GHs.…”
Section: The Red Deer Gh Genementioning
confidence: 99%